Weighted congestion games with separable preferences - Igal Milchtaich (Bar-Ilan University, Department of Economics, 2009)
Players in a congestion game may differ from one another in their intrinsic preferences (e.g., the benefit they get from using a specific resource), their contribution to congestion, or both. In many cases of interest, intrinsic preferences and the negative effect of congestion are (additively or multiplicatively) separable. This paper considers the implications of separability for the existence of pure-strategy Nash equilibrium and the prospects of spontaneous convergence to equilibrium. It is shown that these properties may or may not be guaranteed, depending on the exact nature of player heterogeneity.
Keywords: C72; 330; congestion games; separable preferences; pure equilibrium; finite improvement property; potential; Bottleneck; Spieltheorie; Präferenztheorie; Theorie